Islamic Values in Conservation Biology: Feasibility Analysis of a Religious-Integrated Textbook for Highered Biology Education - Angela, Lia (Department of Biology Education, Faculty of Education and teacher Training, Maritime University of Raja Ali Haji, 2024)
In the era of globalization, biology education faces challenges in integrating modern science with religious values, particularly in the context of conservation biology. The urgency of this research lies in the scarcity of formal biology education literature in Indonesia that incorporates Islamic principles, despite the potential of values such as khalifah fil ardh (stewardship of the earth) and tabdzir (prohibition of wastefulness) to provide ethical guidance for environmental preservation. This study aims to develop and validate a conservation biology textbook based on Islamic values for higher education using the Research and Development (R&D) method with the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The validation process involved five experts evaluating the content, language, presentation, and graphic aspects using a Likert-scale instrument. The results indicate that the textbook achieved a